2016
DOI: 10.1002/adfm.201602125
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive and Environmentally Stable Organic Transparent Electrodes Laminated with Graphene

Abstract: Improving the lifetime and the operational and thermal stability of organic thin-fi lm materials while maintaining high conductivity and mechanical fl exibility is critical for fl exible electronics applications. Here, it is reported that highly conductive and environmentally stable organic transparent electrodes (TEs) can be fabricated by mechanically laminating poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) fi lms containing dimethylsulfoxide and Zonyl fl uorosurfactant (PDZ fi lms) with a monolayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…To realize thermally stable organic electronics, in addition to thermally stable organic semiconductors, the development of electrodes based on organic conductors with thermal robustness is also necessary. Recently, Chu et al developed an environmentally stable and transparent graphene‐laminated polymer‐based conductor. The stable organic conducting layer based on PEDOT:PSS film containing dimethylsulfoxide (DMSO) and Zonyl fluorosurfactant, named as PDZ film was manufactured.…”
Section: Approaches To Overcome the Instability Caused By Degradationmentioning
confidence: 99%
“…To realize thermally stable organic electronics, in addition to thermally stable organic semiconductors, the development of electrodes based on organic conductors with thermal robustness is also necessary. Recently, Chu et al developed an environmentally stable and transparent graphene‐laminated polymer‐based conductor. The stable organic conducting layer based on PEDOT:PSS film containing dimethylsulfoxide (DMSO) and Zonyl fluorosurfactant, named as PDZ film was manufactured.…”
Section: Approaches To Overcome the Instability Caused By Degradationmentioning
confidence: 99%
“…According to the literature, the thickness of the barrier material of Cu should be reduced to < 2 nm to satisfy the requirement of sub−22 nm interconnect technology 1 , 12 . Thus far, graphene (Gr), the thinnest two-dimensional (2D) material known, appears to be the best candidate to satisfy this requirement because of its unique combination of properties that include ultrathin thickness, high carrier mobility, high chemical and thermal stabilities, and impermeability to all atoms, ions, and molecules 13 19 . Furthermore, Gr/Cu composites have the advantages of conducting a high current density with an enhanced thermal reliability compared to that of bare Cu 20 ; in addition, ultrathin graphene films can be directly formed on Cu surfaces with various shapes using a chemical vapor deposition (CVD) process, thereby minimizing any adhesion issues at the interface of graphene and Cu.…”
Section: Introductionmentioning
confidence: 99%
“…Since there are various methods for transferring large‐area graphene onto the top of desired substrates, graphene has also been developed as the transparent conductive top electrodes for organic optoelectronic devices, especially for the semitransparent devices. As a promising replacement of metal top electrodes, graphene has unique nature of ultrahigh transparency, excellent flexibility, and air stability with impermeability to gas and liquid . For the first time, Lee et al reported semitransparent OSCs with top laminated graphene anode .…”
Section: Graphene As Tces For Organic Optoelectronic Devicesmentioning
confidence: 99%